Tinjauan Hukum Hak Asasi Manusia terhadap Larangan Kepemilikan Tanah bagi Warga Negara Indonesia Nonpribumi untuk Keturunan Arab di Daerah Istimewa Yogyakarta - Nadia Isad Farah (Jurnal Hukum Lex Generalis, 2022)
For non- Indigenous Indonesian citizens of Arab descent, to have land rights until now is still based on the Instruction of the Deputy Governor of DIY Number K.898/I/A/1975. Based on these provisions, non-native Indonesian citizens of Arab descent cannot have land rights, and if the descendants of Indonesian citizens who have owned property rights prior to the issuance of the Instruction of the Deputy Governor of DIY Number K.898/I/A/1975, are required to relinquish their property rights to the state for converted into other land rights. This is a form of discrimination and is against the principles of human rights.